The Effects of the International Contract for Sale of Goods - BERLINGHER, Daniel (Journal of Legal Studies, 2018)
The contracts are the indispensable legal instruments for any economic transaction. The international sale contract is the main legal instrument by which international commerce is carried out and through which the movement of goods from producer to consumer is ensured within cross-border relations. The sale contract in international commerce is the legal act by which the parties, the seller and the buyer, belonging to different states, commit each other to transfer the property of a good in return for payment of a price. Regarding the general rules applicable to the contract of international sale of goods, they are regulated by the "United Nations Convention on Contracts for the International Sale of Goods from Vienna". The Convention has adopted uniform rules to govern the international sale of goods contract, if the parties have not chosen expressly for the application of other rules. In this study I present the effects of international sale of goods in the light of the rules of the Vienna Convention of 1980.